Efektivitas Penggunaan Mind Mapping dan Guide Note Taking Berbantuan Canva terhadap Kreativitas Siswa pada Pembelajaran Pendidikan Pancasila di Kelas IV Sekolah Dasar - Shalma Hudi Cahyani; Agustina Tyas Asri Hardini (Journal on Education, 2024)
This research is motivated by the low level of student creativity in learning Pancasila Education in elementary schools. The purpose of this study was to assess the effect of Mind Mapping and Guide Note Taking methods supported by Canva on the creativity of fourth grade students. The research used a type of quasi-experimental research with a nonequivalent control group design. Data were collected using questionnaire technique with 47 students as respondents. The results showed that experimental group 1 had an average pretest score of 62.63 and a posttest score of 70.79; experimental group 2 had an average pretest score of 60.52 and a posttest score of 67.78. Hypothesis testing resulted in a Sig.2 value of 0.034 for both groups. The one-way test indicated that Ho was rejected and Ha was accepted with a significance value of 0.034 divided by 2, resulting in a value of 0.017, which is smaller than 0.05. This indicates that Mind Mapping is better than Guide Note Taking with the help of Canva in improving the creativity of fourth grade students in Pancasila Education.